FAKTOR-FAKTOR YANG MEMENGARUHI PENDAPATAN ASLI DAERAH KOTA PAREPARE - Henriansa, Henriansa (Cateris Paribus Journal, 2021)
PAD as one of the regional acceptances reflects the level of regional self-reliance. The larger pad then shows that the area is able to implement fiscal decentralization and the reliance on the central government is reduced. PAD is defined as acceptance from sources within its own territory, collected under applicable law. The goal that is wanted to be achieved in this study is to analyze the factors that affect PAD. These factors include: government spending, population and GDP. The data observed in this study is a time flat in the period 2008-2017. The estimation model used is multiple regression by using the T and F test in testing the research hypothesis. Based on the results of the analysis, it can be concluded:1) PDRB variable has a positive effect on PAD in Parepare City 2) Government Expenditure Variable has a positive effect on PAD in Parepare city 3) Population variable has no effect on PAD in Parepare city